Social justice, activism, and diversity in U.S. media history
1 online resource
Keywords: "This book offers a diverse approach to journalism history told from a multimedia perspective, re-examining mainstream stories and highlighting contributions that are often overlooked. Interactive and accessible, Social Justice, Activism and Diversity in U.S. Media History is an indispensable resource for Generation Z, scholars in mass communication and American history, journalists and general readers"--